Should I stay, or should I go? - Silverberg, Sarah (Canadian Medical Education Journal, 2019)
In this narrative, I explore the thoughts and emotions that drive the decision of whether to transfer residency programs. I focus on the difficulty of making a career decision with limited information, and the difficulty of exploring the possibility of a transfer while still remaining part of an ongoing residency program. Although residency transfers are a taboo topic, they are remarkably common. Many residents go through this process feeling alone; I hope to convey that these feelings are common. More understanding of the transfer process is needed, particularly in light of the ongoing unmatched Canadian medical graduate crisis and in light of high rates of burnout, to understand the drivers behind resident wellness and satisfaction.